N-salicylidene anilines and their copper complexes: comparative investigations of mesomorphic, morphologic, thermotropic and thermodynamical properties - Nesrullajev, A; Eran, BB (TAYLOR & FRANCIS LTD, 2006)
In this work comparative studies of the mesomorphic and morphologic properties and thermal behaviour of new Schiff base N-salicylidene aniline ligands and the effects of Cu(II) additions on these properties have been carried out. Peculiarities of phase transformations between smectic and nematic mesophases, smectic mesophase and isotropic liquid and nematic mesophase and isotropic liquid during both heating and cooling of N-salicylidene aniline ligands and their Cu(II) complexes have been investigated. The studies have been carried out using polythermic polarizing microscopy, DSC analysis and a capillary temperature wedge.
Keywords: LIQUID-CRYSTALLINE PROPERTIES; PHASE-TRANSITION; ISOTROPIC-PHASE; LANDAU MODEL; PECULIARITIES; BEHAVIOR; Chemistry; Physics